Driving entrepreneurship post COVID-19: Exploring opportunities, confronting challenges and fostering success - Maity, Rittick; Arshada Nadia, Abdullah; Kumaramasy, Sudhakar (UKM Press, 2024)
An entrepreneur is an individual or a set of individuals who manage, create and take the risks of running a business or enterprise. During COVID-19, entrepreneurial growth was slow across the Association of South East Asian Nations (ASEAN), but after post-COVID-19, entrepreneurial growth will accelerate. The paper discusses how market demand, financial management, technological and digital transformation, adaptability and resilience affect the growth and vision of an entrepreneur post-COVID-19. The paper focuses on how social and individual enterprises can transform their mindsets using digitalisation and ICT technologies. Indonesia and Thailand are prominent countries that thrive in growth and are easy to finance. Further, innovation and economic dynamism in this country will provide resilience and positively impact enterprises' growth.